Respostas
respondido por:
6
x - 3 = 3/5.(x + 3)
x - 3 = 3x/5 + 9/5
x - 3x/5 = 9/5 + 3
5x - 3x/5 = 9+15/5
2x/5 = 24/5
10x = 120
x = 12
x - 3 = 3x/5 + 9/5
x - 3x/5 = 9/5 + 3
5x - 3x/5 = 9+15/5
2x/5 = 24/5
10x = 120
x = 12
respondido por:
1
Igualdade de frações temos uma proporção
(x-3)/(x+3)=3/5
5(x-3)=3(x+3)
5x-15=3x+9
5x-3x=9+15
2x=24
x=24/2
x=12
Logo x = 12
(x-3)/(x+3)=3/5
5(x-3)=3(x+3)
5x-15=3x+9
5x-3x=9+15
2x=24
x=24/2
x=12
Logo x = 12
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás